2007
DOI: 10.1242/jcs.03343
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 increases the sensitivity of prostate cancer cells to TNFα-induced apoptosis

Abstract: To examine the effects of increased expression of connexin43 (Cx43) upon cell viability and response to cytotoxic agents, we expressed Cx43 in LNCaP and PC3 prostate cancer cells by infection with a recombinant adenovirus (Ad-Cx43). Infection with Ad-Cx43 led to the formation of Cx43-containing gap junction plaques at appositional membranes and increased Lucifer Yellow transfer in LNCaP cells, but not in PC3 cells. The increased intercellular communication was blocked by co-infection with an adenovirus contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 64 publications
5
41
0
Order By: Relevance
“…They have either agonising or antagonising effects on phases of healing, they can be -pro inflammatory or anti-inflammatory, profibrotic or antifibrotic, pro-proliferative or -anti proliferative…etc [41][42][43][44][45][46][47][48]. The Wound healing requires a balance between these endogenously produced mediators [43][44][45][46][47][48] to progress in a coordinated manner without complications [2,33,34]. The basic Collagen bundles arranged in a reticular pattern closely resembling that of the normal dermis resulting in dermis indistinguishable from that the of surrounding unwounded skin.…”
Section: Discussionmentioning
confidence: 99%
“…They have either agonising or antagonising effects on phases of healing, they can be -pro inflammatory or anti-inflammatory, profibrotic or antifibrotic, pro-proliferative or -anti proliferative…etc [41][42][43][44][45][46][47][48]. The Wound healing requires a balance between these endogenously produced mediators [43][44][45][46][47][48] to progress in a coordinated manner without complications [2,33,34]. The basic Collagen bundles arranged in a reticular pattern closely resembling that of the normal dermis resulting in dermis indistinguishable from that the of surrounding unwounded skin.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 3 showed that Cx43 increased the sensitivity of prostate cancer cells to tumour necrosis factor-a-induced apoptosis. Fukushima et al 1 showed that combination therapy of Cx43 and docetaxel was significantly more cytotoxic when cells were treated with docetaxel after 24 h of Cx43 transfection, suggesting that Cx43 affected sensitivity to docetaxel.…”
Section: Connexin43 In Prostate Cancer G Benko Et Almentioning
confidence: 99%
“…[1][2][3] The channels are bicellular structures formed by the members of a family of about 20 related but distinct Cxs. 4,5 Six Cx monomers assemble to form a hemi-gap junction channel or connexon, which, in turn, forms a complete gap junction channel by docking with connexon from an adjacent cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that gap junctions increase the sensitivity of prostate cancer cells to tumor necrosis factor-α-induced apoptosis (14). Such a "bystander" effect has also been observed for ionizing radiation, in which cells not irradiated but coupled to irradiated cells become damaged or die (15)(16)(17).…”
mentioning
confidence: 92%